PERANCANGAN SISTEM HIDROLIK PADA MESIN PRESS BAMBU LAMINASI - Gumilang, Theo Satria; Krisnaputra, Radhian; Sugiyanto, Sugiyanto; Hendaryanto, Ignatius Aris; Irawati, Inggar Septhia; Bahari, Galuh (Jurnal Rekayasa Mesin, 2023)
The hydraulic system is a power transmission system by using the compressive energy of the fluid into mechanical energy to obtain a power greater than the initial power released. The press machine is one of the pieces of equipment that apply the hydraulic system. In the process of making laminated bamboo, the bamboo gluing technique is assisted using a press machine. Based on observations, the press machine used is a manual press machine, so the pressing process is not efficient. This study aims to increase the effectiveness of pressing laminated bamboo. The results of the study found that the press machine has 4 hydraulic cylinders so the pressing process can be carried out at several points simultaneously. The results of the hydraulic system analysis diagram show hydraulic cylinder moves in 16,9 seconds with a pressure of 100 bar, so the pressing process is fast. Mathematical calculations produce data, a hydraulic gear pump with a displacement of 13 cc/rev, electric motor power of 3,7 kW, hydraulic cylinder diameter of 63 mm, cylinder rod of 35 mm, rod of 400 mm, and a hydraulic tank capacity of 12 liters.